Functional and phylogenetic assembly in a Chinese tropical tree community across size classes, spatial scales and habitats. (30th October 2013) - Yang, Jie; Zhang, Guocheng; Ci, Xiuqin; Swenson, Nathan G.; Cao, Min; Sha, Liqing; Li, Jie; Baskin, Carol C.; Slik, J.W. Ferry; Lin, Luxiang; Poorter, Lourens
Summary Increasingly, ecologists are using functional and phylogenetic approaches to quantify the relative importance of stochastic, abiotic filtering and biotic filtering processes shaping the pattern of species co‐occurrence. A remaining challenge in functional and phylogenetic analyses of tropical tree communities is to successfully integrate the functional and phylogenetic structure of tree communities across spatial and size scales and habitats in a single analysis. We analysed the functional and phylogenetic structure of tree assemblages in a 20‐ha tropical forest dynamics plot in south‐west China. Because the influence of biotic interactions may become more apparent as cohorts age, on local scales, and in resource‐rich environments, we perform our analyses across three size classes, six spatial scales and six distinct habitat types, using 10 plant functional traits and a molecular phylogeny for the >400 tree taxa found in the plot. All traits, except leaf area and stem‐specific resistance, had significant, albeit weak phylogenetic signal. For canopy species, phylogenetic clustering in small and medium size classes turned to phylogenetic overdispersion in the largest size class and this change in dispersion with size was found in each habitat type and across all spatial scales. On fine spatial scales, functional dispersion changed from clustering to overdispersion with increasing size classes. However, on larger spatial scales assemblages were functionally clustered for all size classes and habitats. Phylogenetic and functional structure across spatial and size scales and habitats gave strong support for a deterministic model of species co‐occurrence rather than for a neutral model. The results also support the hypothesis that abiotic determinism is more important at larger scales, while biotic determinism is more important on smaller scales within habitats.